Update on the Financing of the Fund's Concessional Assistance and Debt Relief to Low-Income Member Countries. (Policy Papers; Policy Paper ;, 2010)
This paper updates the quota data base through 2008 and discusses implications for members' calculated quota shares. A subsequent staff paper will review key issues related to the realignment of quota shares and present additional illustrative simulations, for discussion by the Committee of the Whole in early July.